novel maternal lineage revealed in sheep (Ovis aries) - Guo, J; Du, L.X; Ma, Y.H; Guan, W.J; Li, H.B; Zhao, Q.J; Li, X; Rao, S.Q (Animal genetics, 2005)
It is generally believed that domestic sheep have two maternal lineages (haplotypes A and B), based on mitochondrial DNA analysis. In the present study, we provide evidence that a novel maternal lineage (haplotype C) is exhibited in Chinese native sheep. To verify this finding, 231 samples were collected from six Chinese local breeds, which cover the vast geographical region of sheep inhabitation in China. For comparison, 50 samples were collected from two Western breeds collected in China. Mitochondrial DNA was screened by PCR single-strand conformational polymorphism (SSCP), leading to the identification of novel band patterns in ND2 and ND4 genes in the Chinese breeds. Interestingly, mutations at the two loci were in strong linkage disequilibrium. Direct sequencing of the DNA fragments revealed a non-synonymous substitution in ND2. Furthermore, two synonymous mutations were identified by comparisons of the novel type (haplotype C) and the established types (haplotypes A and B). The entire mitochondrial control region for 55 samples was then sequenced to construct a phylogenetic tree and median joining network. Both the tree and network demonstrated a topology of three groups, which is in consistent with the SSCP analysis. Unlike Western breeds, Chinese breeds are composed mainly of haplotypes A and B, but with a small fraction of haplotype C. According to Fu's test and mismatch distribution, haplotype C has not been subject to a recent population expansion. Based on these results, we propose a novel origin for Chinese sheep.